Effects of Regulated Deficit Irrigation on yields, berry quality, and resource use efficiency in the everbearer strawberry Malling Ace under long-term production in TCEA - Kouloumprouka Zacharaki, Aikaterini; Taylor, June M.; Davies, Michael J.; Else, Mark A. (Frontiers in Horticulture, 2025)
The effects of Regulated Deficit Irrigation (RDI) on Class 1 yield, berry quality, and resource use efficiency of Malling Ace, an everbearer strawberry cultivar, were tested in a Total Controlled Environment Agriculture (TCEA) system over a cropping period of 10 months. An automated sensor-based irrigation system was used to ensure coir water and nutrient availability were optimal in the control (well-watered, WW) treatment. The extent of imposed coir drying in the RDI treatments was informed by identifying the coir volumetric moisture content value at which changes in midday stem water potential were first detected in response to gradual coir drying. Two RDI treatments were then imposed under standard TCEA conditions for strawberry. In RDI-1, plants received irrigation to raise the coir volumetric moisture content to a value midway between the irrigation set point and WW values. In RDI-2, irrigation was applied to maintain coir volumetric moisture content within a narrow range from the set point. All RDI treatments were imposed using the automated sensor-based fertigation system. In a second TCEA experiment, the RDI-1 treatment was imposed during a split photoperiod (two light and two dark periods in 24 h). In each experiment, treatment effects of RDI on leaf gas exchange were determined, as were those on Class 1 yields and berry quality. A series of Key Performance Indicators were calculated and compared between treatments and with those from conventional polytunnel strawberry production. The cropping potential of well-watered Malling Ace grown for 12-months in TCEA was quantified. Total Class 1 berry yields per plant were reduced by 30–36% in the RDI treatments due to a combination of lower berry fresh weight and fewer Class 1 berries. Berry soluble solids content was unaffected. Under the split photoperiod, Class 1 yields and berry quality attributes were similar, with water and nutrient use efficiencies being higher in the RDI-treatment. The mean cropping potential of Malling Ace grown for 12 months in TCEA was 3.3 kg of Class 1 fruit per plant, which equates to 39.7 kg per m². After the first cropping flush, the cumulative Class 1 fruit yield per plant was linear.